A Review on Machine Translation in Indian Languages - Chopra, D.; Joshi, N.; Mathur, I. (Engineering, Technology & Applied Science Research, 2018)
Machine translation (MT) is considered an important task that can be used to attain information from documents written in different languages. In the current paper, we discuss different approaches of MT, the problems faced in MT in Indian languages, the limitations of some of the current existing MT systems, and present a review of the work that has been done until now in MT in Indian language perspective.